(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
In the present study matrix and triple layer matrix tablets of metoprolol tartrate were formulated by using xanthan gum as the matrix forming agent and Sodium Carboxy Methyl Cellulose (Na CMC) as barrier layers. The prepared tablets were analysed for their hardness, friability, drug content and in-vitro drug release studies. Marked differences in dissolution characteristics of (M3) and (M3L3) were observed and showed a significant difference statistically. Mean dissolution time (MDT) for M3 and M3L3 were found to be 4.02h and 12.75h, while dissolution efficiency (DE8%) decreased, indicating that the release of metoprolol tartrate is slower from triple layer matrix tablets. The finding of the study indicated that the matrix tablets prolonged the release, but predominantly in a first order kinetics. Layering with Na CMC granules on the matrix core, provided linear drug release with zero order kinetics. The triple layer matrix tablets (M3L3) shows precise controlled release of the drug than that of plain matrix tablets. FT-IR and DSC studies confirmed that there was no chemical interaction between drug and excipients used in the formulation.